Penggunaan Google Classroom pada Pembelajaran Kimia - Novrita Mulya Rosa; Ahmad Suryadi (Jurnal Ilmiah Profesi Guru (JIPG), 2022)
One of the government’s policy to decide the spread of Covid-19 is the learning in schools is carried out online. In managing distant teaching and learning, the most common Learning Management System used nowadays is Google Classroom. This study aims to describe the influence of google classroom on learning chemistry students grade III of Mathematics Education Study Program FMIPA University of Indraprasta PGRI. This was descriptive research with the design of One Shot Case Study The subjects in this study were Semester III students who were programming basic chemistry lesson Mathematics Education Study Program in the scope 70 people in the FMIPA University of Indraprasta PGRI. The Instrument were used in this study in the form learning outcomes tests and the students’ perception on using google classroom questionnaire sheets. The average score of students learning outcomes was 79,76 in the high category. The percentage of student response value was 85,73% in the very good category. The results showed that there was significant effects of student learning outcomes after applying google classroom learning. This is indicated by the value of tcount = 39,587 with a p – value = 0,002.